The Effect of Gross Profit to Predict Operating Cash Flow at PT. Unilever Indonesia TBK - Anita Nisa Kambey; Gebriany Pirade Wenur; Michelle Eliza; Prisca Patricia Liem; Fricy O. Rumintjap (Dharma Ekonomi, 2024)
This study aims to analyze the effect of gross profit on the prediction of operating cash flow at PT. Unilever Indonesia. Gross profit is calculated as the difference between revenue and cost of goods sold, including cash and credit sales, indicating the potential cash inflows expected from customers in the future. The study uses a quantitative method with secondary data obtained from PT. Unilever Indonesia's official website. The results show gross profit significantly impacts the company's operating cash flow prediction. Over the last five years, PT. Unilever Indonesia’s gross profit has increased by an average of 2% per year since 2019. Meanwhile, operating cash flow, calculated from customer receipts and various operational payments, shows fluctuations, with a 3% increase in 2019 and 2021 but only a 1% increase in 2022-2023. This decrease is due to differences in the payment of remuneration to directors and employees, which affects cash flow. These findings highlight the importance of gross profit in predicting operating cash flow in the future.